SYNOPSIS TO THE INDIAN GENERA OF THE FISHES OF THE FAMILY SCIAENIDAE - Lalmohan, R S (Indian Journal of Fisheries, 2011)
Thirty species of sciaenid fishes so far known from India are classified under 14 genera based on the structure of air bladder, otolith and sensory pores. A synoptic key to the subfamilies and genera is given.